Are they give you wings or cut you down - an analysis of the effects of energy drinks on human health - Konrad Białogłowski; Kamila Giżewska; Karol Bochyński; Michał Dacka; Paulina Dąbrowska; Michał Żuber; Katarzyna Molenda; Barbara Borodziuk; Filip Borodziuk; Katarzyna Ciuba (Nicolaus Copernicus University in Toruń, 2024)
This work aims to study the effects of energy drink consumption on human health. In recent years, the consumption of energy drinks has increased significantly, which has sparked the interest of scientists and health experts. In Poland and a few other countries, new laws have been applied to regulate the consumption of energy drinks by minors. In this review paper, we analyze the available scientific research on the effects of energy drinks on physical and mental health. In this paper, we focus on the potential benefits and risks of consuming energy drinks, and the common and dangerous combination with alcohol. We discuss the effects of caffeine, taurine, guarana and other ingredients on the body, and their potential side effects. In addition, we consider the effects of these beverages on the cardiovascular system, cognitive ability, and possible health effects associated with excessive consumption. The conclusions of this work can help to understand the complex health effects of energy drinks and draw attention to the need for caution and moderation in their consumption. Ultimately, this work aims to provide up-to-date knowledge on this issue to assist in making informed decisions about energy drink consumption in the context of a healthy lifestyle.